GE_GERICHTE P/16003/2015 vom 24. Oktober 2018 - GE Cour de justice (2018)
PRÉSOMPTION D'INNOCENCE ; CONTRAINTE(DROIT PÉNAL) ; ENLÈVEMENT(INFRACTION) ; DÉPENS ; COMPENSATION DE CRÉANCES | LCR.90; CP.181; CP.183; CPP.10.al3; CPP.429.al1.leta; CPP.442.al4; CPP.136.al2.leta; CPP.136.al2.letb; CPP.436.al2